Environment management system implementation in selected Malaysian local authorities / Corina Joseph … [et al.] - Joseph, Corina; Jonathan, Lulu; Nichol, Esmie Obrin (2014)
The Government has introduced five major initiatives to transform the nation - 1 Malaysia, the New Economy Model (NEM), the Government Transformation Programme (GTP), the Economic Transformation Plan (ETP) and the Tenth Malaysia Plan (Anuar, 2011). The NEM lists out 8 Strategic Reform Initiatives (SRI) to drive the Malaysian economy towards a higly income, inclusive and sustainable economy. One of the initiatives is strengthening the public sector via numerous public sector reforms agenda, for example, the implementation of environmental management system (EMS). Local authority is chosen as a sample because of its importance role in advancing towards sustainable development. Moreover, only three (out of 149) local authorities in Malaysia to date have implemented EMS. The three local authorities are: Dewan Bandaraya Kuching Utara (DBKU), Majlis Perbandaran Seberang Perai (MPSP) and Majlis Perbandaran Pasir Gudang (MPPG).. This research seeks to examine the adoption of an environmental management system (EMS) in three local authorities in Malaysia and identify the key factors that contribute to successful adoption. In-depth interviews are necessary to obtain first hand information from local authorities involved in the EMS implementation. The aim of these interviews is to document the progress being made by the departments/agencies with their EMS implementation. Data will be collected through semi-structured interviews conducted with environmental coordinators / staff involved in the EMS implementation in DBKU, MPSP and MPPG.